Wayang in Sundanese Dance of Priangan Style - Rusliana, Iyus (TAWARIKH, 2017)
ABSTRACT: This paper is a study of the potential of âwayangâ (puppet show) in Sundanese culture of Priangan subcultures, especially in the art of dance. Initially, the word âwayangâ was interpreted to refer to dolls made of wood which are played by a puppeteer in a puppetry art show or to appoint the plot which is delivered by the puppeteer in a puppetry art show, and also can be directly identified with the performance of puppetry art of âwayang golekâ (wooden puppet show). Furthermore, the potential of âwayangâ has a strong influence or contribution to some aspects of life with some kinds of belief and also of art, including the growth of âwayangâ in Sundanese dance of Priangan style. Because âwayangâ implicitly contains religious meaning in the contents of the plot, so âwayangâ in Sundanese dance of Priangan style cannot be separated from the mission or moral value towards the guidance of life. The origin of âwayang wongâ (men/women puppet show) of Priangan was revealed as a form of dance drama show with the dialogue delivering puppet stories, either completely or partially, in which the scenes are composed in phases and there are always battles or conflicts between the evil characters and the eradicators of the evil. In addition, it was also revealed the richness of the performance forms that only describes a single moment of the puppet story, called a free dance, in the forms of single dance, dance in pairs, and dance in groups or mass dance. KEY WORDS: Wayang; Sundanese Culture; Priangan Subculture; Wayang Dance; Priangan Style.About the Author: Prof. Dr. Iyus Rusliana is a Lecturer at the Department of Dance ISBI (Institut Seni dan Budaya Indonesia or Indonesia Institute of Art and Culture) Bandung, Jalan Buahbatu No.212 Bandung, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: iyus_rusliana@isbi.ac.idRecommended Citation: Rusliana, Iyus. (2017). âWayang in Sundanese Dance of Priangan Styleâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.59-70. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Article Timeline: Accepted (March 9, 2017); Revised (July 3, 2017); and Published (October 28, 2017).